Case report: Extracorporeal life support as a successful bridge to recovery in an incident case of pulmonary arterial hypertension - Pequignot, Benjamin; Chaouat, Ari; Chabot, François; Levy, Bruno; Valentin, Simon (Frontiers in Medicine, 2024)
Pulmonary arterial hypertension (PAH) is characterized by a progressive increase in pulmonary vascular resistance (PVR) due to vascular remodeling of the small pulmonary arteries. In advanced RV failure or severe hypoxemia, Extra Corporeal Life Support (ECLS) is now to be considered, with the objective to bridge patients back to their baseline clinical state while waiting or right after lung transplantation, or bridge to pharmacological optimization of PAH (i.e., bridge to recovery). We describe herein a case of a 30-year-old woman (gravida 6, para 6) with an incident case of heritable PAH revealed by refractory hypoxemia. Despite the use of mechanical ventilation and fluid optimization, patient remained profoundly hypoxemic. ECLS was then initiated to avoid tissue hypoxia. The mechanical option chosen was peripheral femoro-femoral venoarterial extracorporeal membrane oxygen (VA-ECMO), percutaneously implanted. Due to the absence of evidence of chronic respiratory disease or chronic thromboembolic pulmonary hypertension, this severe pre-capillary pulmonary hypertension was attributed to PAH. Therefore, epoprostenol infusion and an association of oral treatments (bosentan and tadalafil) were administered. A dramatic improvement was observed allowing decannulation seven days after initiation of pharmacological treatment. After 29 days, the patient was discharged from hospital with epoprostenol, bosentan and tadalafil. The assessment has been completed by the positive research of mutation (c.741C>G, p.Tyr247) corresponding to a loss of function of the Bone Morphogenetic Protein Receptor 2 (BMPR2) gene. The final diagnosis was heritable PAH. The use of ECLS has been well demonstrated in patients with PAH complicated by an acute RV failure or refractory hypoxemia in “bridge-to-transplantation” strategy. Only few reports have described the use of ECLS as a “bridge-to-recovery” with PAH drugs in untreated or in undertreated PAH patients but none has described such a rapid improvement with resolution of refractory hypoxemia. More studies are needed to assess benefits and limitations of “bridge-to-recovery” strategy and to identify the patients most likely to benefit from it.